2012
DOI: 10.1002/hyp.8414
|View full text |Cite
|
Sign up to set email alerts
|

A nonlinear function approach for the normalized complementary relationship evaporation model

Abstract: Abstract:A nonlinear function approach for the normalized complementary relationship evaporation model that is different from the methodology maintaining the symmetric complementary relationship with appropriate definitions of potential and wetenvironment evaporation is proposed and verified. This approach employs the definitions used in the advection-aridity model, wherein the potential is estimated using the Penman equation. Normalized by Penman potential evaporation, the complementary relationship model is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
135
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(137 citation statements)
references
References 36 publications
1
135
1
Order By: Relevance
“…In Scenario 1, the modified GG model of is used for direct comparison and this scenario used all 75 AmeriFlux sites (36 dry and 39 wet sites). In Scenario 2, the original GG model described by Han et al (2012) (also called the normalized complementary method) and the CRAE method of are used for comparison. Scenario 2 used only 59 sites (29 dry and 30 wet sites) since only these 59 sites have incident global radiation data required by the CRAE model.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Scenario 1, the modified GG model of is used for direct comparison and this scenario used all 75 AmeriFlux sites (36 dry and 39 wet sites). In Scenario 2, the original GG model described by Han et al (2012) (also called the normalized complementary method) and the CRAE method of are used for comparison. Scenario 2 used only 59 sites (29 dry and 30 wet sites) since only these 59 sites have incident global radiation data required by the CRAE model.…”
Section: Resultsmentioning
confidence: 99%
“…Han et al (2012) developed the normalized complementary method which is based on the CRAE method. This study found that the method performed better than the AA model in predicting ET under dry and wet conditions.…”
Section: Scenario 2: Comparison With Other Complementary Methodsmentioning
confidence: 99%
“…Recently, there have been several attempts to improve the complementary relationship and its predictive power of different ET definitions (see Brutsaert and Stricker, 1979;Granger and Gray, 1989;Morton, 1983). Han et al (2012) developed a nonlinear approach to the complementary relationship but the results require further study and verification. Yet, Lhomme and Guilioni (2010) proposed a different model that can describe the complex relationship between ET and ETP based on the convective boundary layer.…”
Section: Complementary Relationshipmentioning
confidence: 99%
“…e PM-Katerji model had poor estimation results when the variation of the evapotranspiration ratio was larger. Han et al [11] first proposed boundary conditions in the formulation of a complementary relationship model. Based on the model by Han et al [11], Brutsaert [2] set physical constraints for the ratio of actual evapotranspiration to possible evapotranspiration, as well as the ratio of wet evapotranspiration to evapotranspiration, and proposed a generalized complementary correlation principle.…”
Section: Introductionmentioning
confidence: 99%
“…Han et al [11] first proposed boundary conditions in the formulation of a complementary relationship model. Based on the model by Han et al [11], Brutsaert [2] set physical constraints for the ratio of actual evapotranspiration to possible evapotranspiration, as well as the ratio of wet evapotranspiration to evapotranspiration, and proposed a generalized complementary correlation principle. Crago et al [12] revised the generalized complementary principle of Brutsaert [2] and concluded that when the actual evapotranspiration was close to 0, the ratio of wet evapotranspiration to possible evapotranspiration is not 0, but between 0 and 1. e revised model was tested using depth and precipitation data from the United States.…”
Section: Introductionmentioning
confidence: 99%